Necking in extrusion film casting: the role of macromolecular architecture - Pol, Harshawardhan V.; Thete, Sumeet Suresh; Doshi, Pankaj; Lele, Ashish K. (Journal of Rheology, 2013)
Extrusion film casting (EFC) is used on an industrial scale to produce several thousand tons of polymer films and coatings. While significant research has been carried out on necking of films of viscoelastic melts in EFC, the influence of macromolecular chain architecture on the necking behavior is not yet fully understood. In the present research, we have explored experimentally and theoretically the effects of long chain branching and molecular weight distribution on the extent of necking during EFC. Polyethylenes of essentially linear architecture but having narrow and broad molecular weight distributions, and polyethylenes having long chain branching were used for experimental studies. The EFC process was analyzed using the one-dimensional flow model of Silagy et al. [Polym. Eng. Sci. 36(21), 2614-2625 (1996)] in which multimode molecular constitutive equations namely the ``extended pom-pom'' equation (for long chain branched polymer melts) and the ``Rolie-Poly (Rouse linear entangled polymers)'' equation (for linear polymer melts) were incorporated. We show that the model qualitatively captures the salient features of the experimental data thereby elucidating the role of chain architecture on the extent of necking. (C) 2013 The Society of Rheology. [http://dx.doi.org/10.1122/1.4788911]